2018
DOI: 10.1007/s00484-018-1510-x
|View full text |Cite|
|
Sign up to set email alerts
|

Health risk assessment on human exposed to heavy metals in the ambient air PM10 in Ahvaz, southwest Iran

Abstract: Heavy metals (HM) are one of the main components of urban air pollution. Today, megacities and industrial regions in southwest of Iran are frequently suffering from severe haze episodes, which essentially caused by PM-bound heavy metals. The purpose of this study was to evaluate the health risk assessment on human exposed to heavy metals (Cr, Ni, Pb, and Zn) in the ambient air PM in Ahvaz, southwest Iran. In this study, we estimated healthy people from the following scenarios: (S3) residential site; (S2) high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(36 citation statements)
references
References 74 publications
0
36
0
Order By: Relevance
“…Numerous respiratory risk studies have shown the strong association of the PM with increased morbidity and mortality ( Chen et al., 2017b ; Dai et al., 2014 ; Daryanoosh et al., 2018 ; Goudarzi et al., 2018 ; Harrison and Yin, 2000 ; Idani et al., 2018 ; India State-Level Disease Burden Initiative Air Pollution, 2019 ; Landrigan et al., 2018 ; Lu et al., 2015 ; Samet et al., 2000 ; Valavanidis et al., 2008 ; Carugno et al., 2016 ; Lin et al., 2005 ). PM is readily associated with respiratory infections such as chronic obstructive pulmonary disease (COPD) ( Khaefi et al., 2017 ; Ling and van Eeden, 2009 ; MacNee and Donaldson, 2003 ; Ni et al., 2015 ; Wen and Gao, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous respiratory risk studies have shown the strong association of the PM with increased morbidity and mortality ( Chen et al., 2017b ; Dai et al., 2014 ; Daryanoosh et al., 2018 ; Goudarzi et al., 2018 ; Harrison and Yin, 2000 ; Idani et al., 2018 ; India State-Level Disease Burden Initiative Air Pollution, 2019 ; Landrigan et al., 2018 ; Lu et al., 2015 ; Samet et al., 2000 ; Valavanidis et al., 2008 ; Carugno et al., 2016 ; Lin et al., 2005 ). PM is readily associated with respiratory infections such as chronic obstructive pulmonary disease (COPD) ( Khaefi et al., 2017 ; Ling and van Eeden, 2009 ; MacNee and Donaldson, 2003 ; Ni et al., 2015 ; Wen and Gao, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dust deposition over the Arabian Sea can cool the ocean surface, influence the phytoplankton, and affect the chlorophyll blooming (Rashki et al, 2015;Singh et al, 2008). Likewise, mineral dust has been suspected to be one of the most critical health risk factors for pulmonary diseases including asthma and allergies in young as well as older adults and contributes to meningitis in Sistan province of Iran (Goudarzi et al, 2018;Merrifield et al, 2013;Miri et al, 2007;Mohammadi et al, 2015;Naimabadi et al, 2016) and in West Africa (Martiny and Chiapello, 2013). While fossil fuel combustion, traffic emissions, upwind petroleum industry, and gas and oil drilling activities are the primary contributing anthropogenic sources in the Middle East, the war remains can be added to the list for southwest Iran, Iraq, and Syria.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Therefore, these events play an integral role in the Earth system, impacting air chemistry and climate processes, soil characteristics and water quality, nutrient dynamics, and biogeochemical cycling in the ocean and terrestrial environments (Hahnenberger and Nicoll 2012;Middleton and Kang 2017). In addition, DEs affect human and animal health and cause socioeconomic disruptions (Lee et al 2014;Zhang et al 2016;Middleton 2017;Baltaci et al 2020;Goudarzi et al 2018). Furthermore, DEs originating from source regions in Mongolia (MG) and China can affect East Asia's downwind area and the global environment across the ocean (Zhao et al 2014;Zhao et al 2015;Zhu et al 2008;Hahnenberger and Nicoll 2012).…”
Section: Introductionmentioning
confidence: 99%